2008
DOI: 10.1161/atvbaha.108.163592
|View full text |Cite
|
Sign up to set email alerts
|

AP-1–Dependent Transcriptional Regulation of NADPH Oxidase in Human Aortic Smooth Muscle Cells

Abstract: Objective-NADPH oxidase (NADPHox) is the major source of reactive oxygen species in vascular diseases; the mechanisms of enzyme activation are not completely elucidated. AP-1 controls the expression of many genes linked to vascular smooth muscle cells (SMCs) dysfunction. In this study we searched for the role of AP-1 in the regulation of NADPHox expression and function in human aortic SMCs exposed to proinflammatory conditions. Methods and Results-Cultured SMCs were exposed to either angiotensin II (Ang II) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 52 publications
4
73
0
1
Order By: Relevance
“…Next, we examined the expression of the target genes Cox-2 (Ptgs2), Nox-2, and p40 phox . [27][28][29] In keeping with our results, we found that Cox-2, Nox-2, and p40 phox were induced at 3 h after OGD, but induction was impaired in neurons after acute inhibition of TAK1 (Figures 4a-c). However, chronic inhibition of TAK1 did not interfere with the upregulation of Cox-2 and Nox-2, and only partially reduced the induction of p40 phox by OGD in neurons (Figures 4d-f).…”
Section: Resultssupporting
confidence: 88%
“…Next, we examined the expression of the target genes Cox-2 (Ptgs2), Nox-2, and p40 phox . [27][28][29] In keeping with our results, we found that Cox-2, Nox-2, and p40 phox were induced at 3 h after OGD, but induction was impaired in neurons after acute inhibition of TAK1 (Figures 4a-c). However, chronic inhibition of TAK1 did not interfere with the upregulation of Cox-2 and Nox-2, and only partially reduced the induction of p40 phox by OGD in neurons (Figures 4d-f).…”
Section: Resultssupporting
confidence: 88%
“…The integral membrane protein p22 phox is an indispensable component of the superoxide-generating phagocyte NADPH oxidase, which is a central molecule in the production of superoxides. [45][46][47][48][49] Conversely, the expression of antioxidants SOD and TXN decreased significantly in infarcted myocardium of rats exposed to tobacco smoke compared to tobacco naïve.…”
Section: Discussionmentioning
confidence: 97%
“…Our findings of increased mRNA levels in PPHN PA and PASMC suggest that increased transcription and/or increased mRNA stability is involved. Other studies using systemic vascular SMC have shown that p22 phox transcription is activated by several ROSsensitive factors, including NF-jB (28) and AP-1 (27), while Nox4 transcription is upregulated by NFjB (28) and HIF-1a (9). Nox-derived H 2 O 2 is known to amplify its own production via a feed-forward mechanism in vascular disease (8), and exposure to exogenous H 2 O 2 increases superoxide generation via Nox in vascular SMC (25).…”
Section: Nox4 In Pphnmentioning
confidence: 99%